ANALISIS LAPORAN ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PT ASTRA AGRO LESTARI Tbk TAHUN 2020¬¬ -2023 - Anugra, Anugra; Haitamy, Ery Bestary Al; Saputra, Ferdyan Wana (Journal of Applied Accounting And Business, 2025)
This research aims to find out how the financial performance of PT Astra Agro Lestari Tbk is if assessed using cash flow reports and cash flow ratios so that it can assess the company's ability to generate net profits. Looking at financial performance can make it easier for parties in the decision-making process. This type of research is quantitative research. Data collection was carried out by accessing cash flow report data in financial reports taken from the Indonesia Stock Exchange website The type of data used in this research is secondary data. Using cash flow from operating, investment and financing activities as well as ratio analysis, namely the Operating Cash Flow Ratio (AKO), Capital Expenditure Ratio (PM), Total Debt Ratio (TH). Based on research results from the calculation of cash flow reports, it shows that the financial performance of PT Astra Agro Lestari Tbk during the 4 year period 2020-2023 is not good or effective because the ratio value is below number 1 which illustrates that the company is unable to fulfill its obligations and commitments.